Iris Claw versus Scleral Fixation Intraocular Lens Implantation during Pars Plana Vitrectomy - Fereydoun Farrahi; Mostafa Feghhi; Foad Haghi; Ali Kasiri; Abbas Afkari; Mahmood Latifi (Journal of Ophthalmic & Vision Research, 2012)
Purpose: To compare the outcomes of iris claw anterior chamber intraocular lens (ICACIOL) with that of scleral fixation posterior chamber intraocular lens (SF-PCIOL) implantation during pars plana vitrectomy (PPV) as initial surgery to correct aphakia. Methods: Twelve patients with complicated cataract surgery or trauma who had suffered nucleus, whole crystalline lens or intraocular lens (IOL) drop into the vitreous cavity, and undergone PPV with IC-ACIOL implantation over a period of one year were evaluated for the purpose of this study. Uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), central corneal thickness (CCT), spherical equivalent (SE) refractive error, astigmatism and complications were recorded. The results were compared to outcomes of another group of 13 patients who had previously undergone PPV with SF-PCIOL implantation. Results: Mean improvement of UCVA was greater in IC-ACIOL eyes as compared to the SF-PCIOL group (-1.17±0.28 versus -0.89±0.21 logMAR, P=0.01), corresponding values for postoperative BCVA were 0.24±0.17 and 0.44±0.22 logMAR (P=0.041), respectively. Average postoperative SE was comparable in the IC-ACIOL and SFPCIOL groups at 0.6±1.03 and 0.56±1.23 diopters, respectively (P=0.290). However, 10 (83.3%) IC-ACIOL eyes versus 6 (46.1%) SF-PCIOL eyes had SE within 1 diopter of emmetropia (P=0.048). Mean postoperative increase in CCT was comaparble between the study groups (P=0.126). Conclusion: In the absence of sufficient capsular support, the use of an IC-ACIOL for correction of aphakia during PPV can be a good alternative and seems to entail better visual outcomes as compared to SF-PCIOL.